Optimizing heat transfer in a finned rectangular latent heat storage system using response surface methodology - Mohammadreza Ebrahimnataj Tiji; Sina Rezaei; Khashayar Hosseinzadeh; Sami Kaplan; Pouyan Talebizadehsardari; Amir Keshmiri (Case Studies in Thermal Engineering)
This work explores how fin design optimization can improve heat transfer in latent heat thermal energy storage (LHTES) systems. Several fin designs, angles, and arrangements are examined using the Response Surface Methodology (RSM) and the Taguchi technique to optimize energy storage performance. For this purpose, a two-dimensional numerical model is generated to simulate and then optimize the behaviour of the melting process. The numerical simulations are performed using the enthalpy-porosity approach, wherein the phase transition behaviors are effectively modeled by incorporating the energy, momentum, and continuity equations into one analytical framework using the finite volume method. To investigate the effects of find design on the process of melting, three different fin configurations were adopted: Symmetry, Reversed Symmetry, and Left-Sided. Other parametric variations included optimization studies on the height-to-width ratio of the chamber, the angle of the fins, and the distance from the floor that gave the best heat storage performances. The findings show that, in comparison to other designs, a symmetric fin structure with greater fin surface areas at the bottom of the chamber greatly increases melting rates, heat transfer efficiency, and shortens melting times by up to 57 %. Using RSM, the optimal fin arrangement is determined, resulting in a heat exchanger height-to-width ratio of 1.15, a fin angle of 4.31°, and a fin distance of 15.56 mm from the chamber floor. The heat storage rate of the optimum case is 15 % higher than that of the reference case before the optimization and after the initial parametric study. The thermal performance of LHTES systems is improved by this optimized design, increasing their suitability for renewable energy applications.